2015
DOI: 10.1080/09575146.2015.1022513
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring practices in workplace-based professional preparation: a critical analysis of policy developments in the Italian context

Abstract: In recent years, the issue of early childhood staff professionalisation has been taking an increasingly prominent position in policy-making and academic debates at the international level. Despite this growing interest, studies investigating the content and delivery of professional preparation programmes for early childhood practitioners are still quite rare in European literature. Against this background, the article will describe and critically analyse the characterising features of the university degree for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
0
9
0
2
Order By: Relevance
“…En el presente estudio, en el marco de la expectativa de los extensionistas ingresantes de recibir apoyo de sus autoridades inmediatas, profesionales de Argentina y Guatemala reclamaron la falta de orientación, asesoramiento y acompañamiento de sus jefes: "hay coordinadores que dividen sus comunidades: 'a vos te tocan estos grupos' y vos mirás cómo salís" (Gt1-In-H). Tanto en la literatura científica como en las entrevistas se identificó como una de las posibles razones la falta de tiempo (Balduzzi y Lazzari, 2015; Greenhalgh y Rawlinson, 2013) y de motivación (Washington y Cox, 2016) de jefes y mentores.…”
Section: Características De Los Mentores Y Ajuste Mentor-aprendizunclassified
“…En el presente estudio, en el marco de la expectativa de los extensionistas ingresantes de recibir apoyo de sus autoridades inmediatas, profesionales de Argentina y Guatemala reclamaron la falta de orientación, asesoramiento y acompañamiento de sus jefes: "hay coordinadores que dividen sus comunidades: 'a vos te tocan estos grupos' y vos mirás cómo salís" (Gt1-In-H). Tanto en la literatura científica como en las entrevistas se identificó como una de las posibles razones la falta de tiempo (Balduzzi y Lazzari, 2015; Greenhalgh y Rawlinson, 2013) y de motivación (Washington y Cox, 2016) de jefes y mentores.…”
Section: Características De Los Mentores Y Ajuste Mentor-aprendizunclassified
“…Nevertheless, work placement has been considered a relevant part of the higher education professionalisation programmes in cross-national studies (Oberhuemer 2015;Urban et al 2011). Indeed, work placement is recognised as a 'learning space' (Jensen 2015), with opportunities for recursive processes between theory and practice (Balduzzi and Lazzari 2015) and for its debate against beliefs and values . Edwards (1998) argues that partnerships between schools and universities have the potential to be sites of regeneration of professionalism.…”
Section: Introductionmentioning
confidence: 99%
“…Heikkinen, Jokinen, & Tynjälä, 2012). Balduzzi and Lazzarri (2015) have acknowledged that ECEC mentors need to be guided and supported to engage in constructive and reflective dialogue with students. Ukkonen-Mikkola and Turtiainen (2016) have shown that students, mentors, and university lecturers appreciate mentor training.…”
Section: Mentoring As Support In the Professional Development Processmentioning
confidence: 99%
“…Furthermore, Pendergast, Garvis, and Keogh (2011) state that students have the opportunity to face the reality of the role during these practicums. It is thus very important that the practicums in preschools are guided by trained and motivated mentors (Balduzzi & Lazzarri, 2015;Leshem, 2012;Ukkonen-Mikkola & Turtiainen, 2016).…”
Section: Mentor Training In the Context Of Preschool Teacher Educationmentioning
confidence: 99%
See 1 more Smart Citation